Охранные исследования многослойного поселения Песочин-Мобиль 2 под Харьковом в 2008 г. - Шрамко, И.Б.; Задников, С.А. (Археологічні дослідження в Україні, 2009)
The materials on protective archaeology research at the multilayer settlement Pisochyn Mobil 2, discovered on the territory of Kharkiv Region in Kharkiv Oblast, are described in the paper. During the excavations there have been uncovered layers of various periods from the 2 nd millennia BC to the 1 st millennia AD.